The Time Course of Contrast Adaptation Measured with a New Method: Detection of Ramped Contrast. (May 2014) - Dong, Xue; Engel, Stephen A; Bao, Min
The present study introduces a new method to measure contrast detection thresholds before and after adaptation to contrast. A sinusoidal testing grating increased contrast at a constant rate from an initial subthreshold level. Subjects indicated when the grating was just visible, which terminated its presentation. The stimulus contrast at the time of response was taken as a measure of relative threshold. We used the method to measure the time courses of changes in threshold following adaptation, for several adapting contrasts (9, 19, 29, or 39 dB, ref. 1%) and adapting durations (10, 100, or 1000 s). The buildup and decay of adaptation to contrast was described well by a power function of time. These results agree with previous findings, but are more efficient in terms of subject time. This method promises to be a useful tool for studying the dynamics of adaptation to spatial contrast.